Dimensi Manajerial dan Politik Proses Penyusunan dan Penetapan Anggaran Pendapatan dan Belanja Daerah (Studi Ketepatan Waktu Proses Penyusunan dan Penetapan Anggaran Pendapatan dan Belanja Daerah Kabupaten Blitar Tahun Anggaran 2013 -2015) - Laksono, Fia (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The process of preparation and approval of public sector budget is a process that is complicated because in addition to requiring managerial capabilities also political capacity, execute lobby, build coalitions, the expertise to negotiate and understanding of the principle of absolute public financial management is needed. Determination of the late budget will impede the process of public services, and loss of function of the budget as a local economic stimulus driver. Changes in regional governance law of Act 32 of 2004 into Act 23 of 2014 which set of sanctions against the head region and Parliament when the budget late set a positive influence on approval of APBD. Regents and DPRD sanctions to be a motivator area to set the budget on time is different from the determination of the previous year is often too late set.